Aristotle’s Theory of Causes and the Holy Trinity: New Evidence About the Chronology and Religion of Nicolaus “of Damascus” - Fazzo, Silvia; Zonta, Mauro (Laval théologique et philosophique, 2008)
AbstractThe identity and chronology of Nicolaus Peripatheticus, the author of a summary of Aristotle’s philosophy, were recently discussed in a paper by Silvia Fazzo published in the Revue des Études Grecques. The usual dating, based upon the identification of Nicolaus with the famous historian Nicolaus Damascenus, places Nicolaus in the 1st century bc, but Fazzo argues that it is likely that he lived in the period ranging from the 3rd to the 5th centuries ad, and more likely, during the age of the Roman Emperor Julian (361-363 ad). This hypothesis is supported by a new fragment in Hebrew translation, discovered by Mauro Zonta, where Nicolaus gives an explanation of the Christian doctrine of God’s Trinity in terms of Aristotle’s doctrine of causes : God is one, being a single substance, but He is also three, insofar as He is the efficient, formal, and final causes of the world. As far as it is possible for such a short fragment, the authors contend that it is plausible to date it from the age of Julian.